Investigation of multilayer printed circuit board (PCB) film warpage using viscoelastic properties measured by a vibration test. (11th February 2015) - Joo, Sung-Jun; Park, Buhm; Kim, Do-Hyoung; Kwak, Dong-Ok; Song, In-Sang; Park, Junhong; Kim, Hak-Sung
Abstract: Woven glass fabric/BT (bismaleimide triazine) composite laminate (BT core), copper (Cu), and photoimageable solder resist (PSR) are the most widely used materials for semiconductors in electronic devices. Among these materials, BT core and PSR contain polymeric materials that exhibit viscoelastic behavior. For this reason, these materials are considered to have time- and temperature-dependent moduli during warpage analysis. However, the thin geometry of multilayer printed circuit board (PCB) film makes it difficult to identify viscoelastic characteristics. In this work, a vibration test method was proposed for measuring the viscoelastic properties of a multilayer PCB film at different temperatures. The beam-shaped specimens, composed of a BT core, Cu laminated on a BT core, and PSR and Cu laminated on a BT core, were used in the vibration test. The frequency-dependent variation of the complex bending stiffness was determined using a transfer function method. The storage modulus ( E ′) of the BT core, Cu, and PSR as a function of temperature and frequency were obtained, and their temperature-dependent variation was identified. The obtained properties were fitted using a viscoelastic model for the BT core and the PSR, and a linear elastic model for the Cu. Warpage of a line pattern specimen due to temperature variation was measured using a shadow Moiré analysis and compared to predictions using a finite element model. The results provide information on the mechanism of warpage, especially warpage due to temperature-dependent variation in viscoelastic properties.